An ex vivo porcine model of the anterior glottoplasty for voice feminization surgery. (31st July 2019) - Rohlfing, Matthew L.; Kuperstock, Jacob E.; Friedman, Daniel; Spiegel, Jeffrey H.
Abstract : Objective: Perceived gender identity is correctly assigned when a combination of physical and vocal attributes become congruent. Several voice feminization procedures have gained popularity, but current evidence of their impact on vocal feminization is limited to case series. This study establishes an ex vivo porcine phonatory model to evaluate the ideal extent of anterior glottic web formation in relation to frequency elevation and airway patency. Methods: Six fresh porcine larynges were obtained and fitted with arytenoid adduction sutures. Compressed air was passed through the larynges, and the vocal folds were adducted to induce phonation. Vocal fold length, posterior glottic width, fundamental frequency, and sound pressure intensity were measured as the vocal folds were progressively shortened as per the anterior glottic web surgical technique. Results: The average fundamental frequency prior to web formation was 109.7 Hz. The maximum frequency achieved after web formation was 403.7 Hz, and the web proportions varied from 11.8% to 61.0% of the length of the membranous vocal folds. The glottic cross‐sectional area showed an expected inverse linear relationship to the length of the glottic web. Creation of an anterior glottic web caused consistent elevation of pitch, but there was a gradual plateau of effect with increased length of the web. Conclusion: The ex vivo porcine larynx is demonstrated as an effective, available, and low‐cost model for further study of vocal pitch elevation surgical techniques. We demonstrate that in addition to progressively reducing the cross‐sectional area of the airway, additional benefit from increased web length is limited. Level of Evidence: NA Laryngoscope, 130:E206–E212, 2020